2019
DOI: 10.13057/biodiv/d200712
|View full text |Cite
|
Sign up to set email alerts
|

The The structure of mangrove communities in response to water quality in Jakarta Bay, Indonesia

Abstract: Abstract. Sari N, Patria MP, Soesilo TEB, Tejakusuma IG. 2019. The structure of mangrove communities in response to water quality in Jakarta Bay, Indonesia. Biodiversitas 20: 1873-1879. The waters of Jakarta Bay, which is a habitat for mangrove vegetation, have been polluted caused by many human activities such as development of housing, industry, tourism and facilities along the coast, and reclamation of man-made islands. The islands reclamation has caused changes in ocean current pattern and has impacts on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…This study in Surabaya has identified 5 species of mangroves, which is nearly identical to research in the nearest mangrove forest in Pasuruan (Isroni et al 2019). Other studies on the coasts of major cities, namely Jakarta Bay and Muara Kapuk, have identified 5 to 9 mangrove species (Rumondang et al 2021;Sari et al 2019). The number of mangrove species found in remote areas with natural mangrove forests is considerably higher, as evidenced by studies in Mimika Papua (66 species), Segara Anakan Cilacap, Central Java (16 species) and Kutai National Park, East Kalimantan (17 species) (Poedjirahajoe et al 2019;Setyadi et al 2021;Widyastuti et al 2018).…”
Section: Mangrove Community Structuresupporting
confidence: 72%
“…This study in Surabaya has identified 5 species of mangroves, which is nearly identical to research in the nearest mangrove forest in Pasuruan (Isroni et al 2019). Other studies on the coasts of major cities, namely Jakarta Bay and Muara Kapuk, have identified 5 to 9 mangrove species (Rumondang et al 2021;Sari et al 2019). The number of mangrove species found in remote areas with natural mangrove forests is considerably higher, as evidenced by studies in Mimika Papua (66 species), Segara Anakan Cilacap, Central Java (16 species) and Kutai National Park, East Kalimantan (17 species) (Poedjirahajoe et al 2019;Setyadi et al 2021;Widyastuti et al 2018).…”
Section: Mangrove Community Structuresupporting
confidence: 72%
“…Recently mangrove species population in Indonesia has been studied whether a national scale [1], [25], [26] and on at regional scale in Jakarta Bay [3], [11]. Information on the density and NDVI values of R. apiculata from those studies is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mangrove ecosystems, particularly Jakarta Bay, have been conducted by previous studies [11], [12]. Despite large numbers of literature on mangroves, a study focusing on how local communities, mainly fishermen, utilize the mangrove ecosystems is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…It grows well to the interior as long as it still gets a good supply of saltwater. Besides that, according to Sari et al (2019), Srikanth et al (2015, Utina et al (2019), and Syarifuddin and Zulharman (2012) that mangrove plants have unique adaptability to the environment such as adaptation to low oxygen levels, adaptation to high salinity, adaptation to unstable soil.…”
Section: Discussionmentioning
confidence: 99%